Relationship Between Age of Menarche and Regularity of Menstrual Cycle in Female Students At Mts Hasyim Asy'ari Lamongan - Asyaul wasiah; ida Susila (Jurnal Ilmiah Kesehatan, 2026)
Menarche marks the beginning of the maturation of the reproductive hormonal system in adolescent girls. This hormonal system plays an important role in regulating the menstrual cycle. The purpose of this study was to determine the relationship between the age of menarche and the regularity of the menstrual cycle. The research design used a cross-sectional design. This study was conducted at MTs Hasyim Asy'ari, Kembangbahu District, Lamongan. The sample was taken from all 38 female students of grade IX using a simple random sampling method. The independent variable of this study was the age of menarche and the dependent variable was the regularity of the menstrual cycle. Data analysis using the Chi-Square test showed that if the p-value <0.05, then the null hypothesis was rejected, and there was a significant relationship between categorical variables. Based on the results of the Chi-Square test in this study, the Asymp.Sig value was 0.005, which was smaller than 0.05. This indicates that the null hypothesis (H0) can be rejected. Thus, it can be concluded that there is a significant relationship between the age of menarche and the regularity of the menstrual cycle. This means that the age of menarche is correlated with the regularity of the menstrual cycle, indicating that the age of menarche factor can influence the regularity of the menstrual cycle in individuals.